MSME Tax Socialization for Pakuncen Village Communities - Pratiwi, Refi; Puspanita, Intan (MOVE: Journal of Community Service and Engagement, 2024)
In the process of realizing optimal taxpayer compliance in paying taxes, of course the basic factor is the taxpayer's own awareness. Because in fact Taxpayer awareness in paying taxes is the main key to the success of government programs in increasing state income through taxes. Tax outreach for Micro, Small and Medium Enterprises (MSMEs) is very important to help business actors understand their tax obligations. The MSME Tax socialization activity is carried out. The method used in this community service is carried out in several stages. The first stage is identification to find out priority issues that will be resolved through this service. The identification stage was carried out by interviewing MSMEs in Pakuncen Village. The results of this activity introduced MSME Tax to mothers who have businesses so that residents in Pakuncen Village are aware of the importance of taxation, especially for mothers who are working hard. From this socialization there were several participants who felt enthusiastic about the introduction of this taxation because according to the participants they had never before known about the MSME Tax. This is very helpful and motivates local residents to be more active in entrepreneurship so that they can increase their tax obligations because previously socialization has been carried out, in the future there will be more sustainable assistance.